A Novel Synthesis of Disubstituted Quinazoline Diones with Differential N-Substitution via a Copper-Catalysed Cross-Coupling of Acyl Ureas - Durham, Emma; Perkins, Dave; Scott, James S.; Wang, Jimmy; Watson, Sam (Synlett, 2016)
An efficient method for the synthesis of disubstituted quinazoline diones with differential N-substitution is reported. A wide range of substitutions on the aromatic and dione rings are tolerated, and the reaction proceeds in high yields under mild conditions.
Keywords: acyl ureas; quinazoline diones; copper-catalysed; Ullmann; intramolecular cyclisation